196k views
3 votes
Which function is f(x) equal to f^-1(x)?

a. f(x)=x+6/x-6
b. f(x)= x+2/x-2
c. f(x) x+1/x-1
d. f(x) x+5/x-5

User Kianenigma
by
5.3k points

2 Answers

2 votes

Answer:

C. f(x) = x+1/x-1

Explanation:

y = (x+1)/(x-1)

Interchange the x and the y

x = (y+1)/(y-1)

Now, we will solve for y

x(y-1) = y+1

xy - x = y+1

y(x-1) = x+1

y = (x+1)/(x-1)

f^-1(x) = (x+1)/(x-1)

f(x) = f^-1(x)

I hope I helped!

Let me know if you need anything else!

~ Zoe

User Samiron
by
5.0k points
0 votes

Answer:

c. f(x) x+1/x-1

Explanation:

To answer this question, we need to check each answer one by one until we find the right one.

y = (x+6)/(x-6)

switch x and y

x = (y+6)/(y-6)

solve for y

x(y-6) = y+6

xy - 6x = y+6

y(x-1) = 6x+6

y = (6x+6) /(x-1) = 6(x+1)/(x-1)

f^-1(x) = 6(x+1)/(x-1)

y = (x+2)/(x-2)

switch x and y

x = (y+2)/(y-2)

solve for y

x(y-2) = y+2

xy -2x = y+2

y(x-1) = 2x+2

y = (2x+2)/(x-1)

f^-1(x) = 2(x+1)/(x-1)

y = (x+1)/(x-1) ------ correct one

switch x and y

x = (y+1)/(y-1)

solve for y

x(y-1) = y+1

xy - x = y+1

y(x-1) = x+1

y = (x+1)/(x-1)

f^-1(x) = (x+1)/(x-1)

f(x) = f^-1(x)

User Nate Fox
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.